Distinct mechanisms of epithelial adhesion for Candida albicans and Candida tropicalis. Identification of the participating ligands and development of inhibitory peptides. - Bendel, C M (1993)
The yeast Candida albicans is the leading cause of disseminated fungal infection in neonates, immunocompromised hosts, diabetics, and postoperative patients; Candida tropicalis is the second most frequent isolate. Because the integrin analogue in C. albicans shares antigenic, structural, and functional homologies with the beta 2-integrin subunits alpha M and alpha X, we investigated the role of integrin analogues in epithelial adhesion of C. albicans and C. tropicalis. On flow cytometry with the monoclonal antibody (mAb) OKM1, surface fluorescence was highest for C. albicans and significantly reduced for C. tropicalis (P < 0.001). However, adhesion to the human epithelial cell line HeLa S3 did not differ for these two candidal species: specific adhesion was highest for C. albicans at 44.0 +/- 1.8%, and only slightly lower for C. tropicalis at 38.8 +/- 3.6% (P = NS). The disparity between expression of the integrin analogue and epithelial adhesion suggested distinct mechanisms for this process in C. albicans versus C. tropicalis. Preincubation of C. albicans with anti-alpha M mAbs, with purified iC3b (the RGD ligand for the integrin analogue), or with 9-15-mer RGD peptides from iC3b all inhibited epithelial adhesion significantly (P < 0.001-0.04). Purified fibronectin or fibronectin-RGD peptides failed to block C. albicans adhesion. In contrast, epithelial adhesion of C. tropicalis was significantly inhibited by purified fibronectin and its RGD peptides (P < or = 0.021), but not by iC3b nor the iC3b-RGD peptides. Both iC3b and fibronectin were identified on the surface of epithelial cells after growth in serum-free medium. A polyclonal antibody to C3 inhibited C. albicans adhesion while a control antibody to fibronectin was ineffective; the converse was true for C. tropicalis. These results indicate that the pathogenic yeasts C. albicans and C. tropicalis recognize distinct RGD ligands present at the surface of the epithelial cell and that these interactions can be differentially inhibited by defined RGD peptides containing appropriate flanking sequences.